Comparison on losses and flux distribution between two 3-phase distribution transformers 1000kVA assembled with air gap and without air gap of transformer core lamination - Ismail, Daut; Dina Maizana, Maiz Ahmad; Shuhaimi, Zakaria; Soib, Taib (Institute of Electrical and Electronics Engineering (IEEE), 2008)
Link to publisher's homepage at http://ieeexplore.ieee.org